Anaesthesia and orphan disease: Bloom's syndrome - Eberhardt, Esther; Münster, Tino; Wurm, Jochen; Prottengeier, Johannes (European Journal of Anaesthesiology, 2016)
EVALuna2:16727

C-fiber recovery cycle supernormality depends on ion concentration and ion channel permeability - Tigerholm, Jenny; Petersson, Marcus E.; Obreja, Otilia; Eberhardt, Esther; Namer, Barbara; Weidner, Christian; Lampert, Angelika; Carr, Richard W.; Schmelz, Martin; Fransen, Erik (Biophysical Journal, 2015)
Following each action potential, C-fiber nociceptors undergo cyclical changes in excitability, including a period of superexcitability, before recovering their basal excitability state. The increase in superexcitability during this recovery cycle depends upon their immediate firing history of the axon, but also determines the instantaneous firing frequency that encodes pain intensity. To explore the mechanistic underpinnings of the recovery cycle phenomenon a biophysical model of a C-fiber has been developed. The model represents the spatial extent of the axon including its passive properties as well as ion channels and the Na/K-ATPase ion pump. Ionic concentrations were represented inside and outside the membrane. The model was able to replicate the typical transitions in excitability from subnormal to supernormal observed empirically following a conducted action potential. In the model, supernormality depended on the degree of conduction slowing which in turn depends upon the frequency of stimulation, in accordance with experimental findings. In particular, we show that activity-dependent conduction slowing is produced by the accumulation of intraaxonal sodium. We further show that the supernormal phase results from a reduced potassium current Kdr as a result of accumulation of periaxonal potassium in concert with a reduced influx of sodium through Nav1.7 relative to Nav1.8 current. This theoretical prediction was supported by data from an in vitro preparation of small rat dorsal root ganglion somata showing a reduction in the magnitude of tetrodotoxin-sensitive relative to tetrodotoxin -resistant whole cell current. Furthermore, our studies provide support for the role of depolarization in supernormality, as previously suggested, but we suggest that the basic mechanism depends on changes in ionic concentrations inside and outside the axon. The understanding of the mechanisms underlying repetitive discharges in recovery cycles may provide insight into mechanisms of spontaneous activity, which recently has been shown to correlate to a perceived level of pain.
EVALuna2:2478

Gene dosage-dependent rescue of HSP neurite defects in SPG4 patients' neurons - Havlicek, Steven; Kohl, Zacharias; Mishra, Himanshu Kumar; Prots, Iryna; Eberhardt, Esther; Denguir, Naime; Wend, Holger; Ploetz, Sonja; Boyer, Leah; Marchetto, Maria C. N.; Aigner, Stefan; Sticht, Heinrich; et al. (Human Molecular Genetics, 2014)
The hereditary spastic paraplegias (HSPs) are a heterogeneous group of motorneuron diseases characterized by progressive spasticity and paresis of the lower limbs. Mutations in Spastic Gait 4 (SPG4), encoding spastin, are the most frequent cause of HSP. To understand how mutations in SPG4 affect human neurons, we generated human induced pluripotent stem cells (hiPSCs) from fibroblasts of two patients carrying a c.1684C>T nonsense mutation and from two controls. These SPG4 and control hiPSCs were able to differentiate into neurons and glia at comparable efficiency. All known spastin isoforms were reduced in SPG4 neuronal cells. The complexity of SPG4 neurites was decreased, which was paralleled by an imbalance of axonal transport with less retrograde movement. Prominent neurite swellings with disrupted microtubules were present in SPG4 neurons at an ultrastructural level. While some of these swellings contain acetylated and detyrosinated tubulin, these tubulin modifications were unchanged in total cell lysates of SPG4 neurons. Upregulation of another microtubule-severing protein, p60 katanin, may partially compensate for microtubuli dynamics in SPG4 neurons. Overexpression of the M1 or M87 spastin isoforms restored neurite length, branching, numbers of primary neurites and reduced swellings in SPG4 neuronal cells. We conclude that neurite complexity and maintenance in HSP patient-derived neurons are critically sensitive to spastin gene dosage. Our data show that elevation of single spastin isoform levels is sufficient to restore neurite complexity and reduce neurite swellings in patient cells. Furthermore, our human model offers an ideal platform for pharmacological screenings with the goal to restore physiological spastin levels in SPG4 patients.
EVALuna2:2420

Human sensory neurons derived from pluripotent stem cells for disease modelling and personalized medicine - Lampert, Angelika; Bennett, David L.; McDermott, Lucy A.; Neureiter, Anika; Eberhardt, Esther; Winner, Beate; Zenke, Martin (Neurobiology of pain (Cambridge, Mass.), 2020)
In this concise Mini-Review we will summarize ongoing developments of new techniques to study physiology and pathophysiology of the peripheral sensory nervous system in human stem cell derived models. We will focus on recent developments of reprogramming somatic cells into induced pluripotent stem cells, neural differentiation towards neuronal progenitors and human sensory neurons. We will sum up the high potential of this new technique for disease modelling of human neuropathies with a focus on genetic pain syndromes, such as gain- and loss-of-function mutations in voltage-gated sodium channels. The stem cell derived human sensory neurons are used for drug testing and we will summarize their usefulness for individualized treatment identification in patients with neuropathic pain. The review will give an outlook on potential application of this technique as companion diagnostics and for personalized medicine.
Created from Fastlane, Scopus look-up
Keywords: Disease modelling; iPSC; Pain; Peripheral neuron; Stem cell differentiation

Pain relief in a neuropathy patient by lacosamide: Proof of principle of clinical translation from patient-specific iPS cell-derived nociceptors - Namer, Barbara; Schmidt, Diana; Eberhardt, Esther; Maroni, Michele; Dorfmeister, Eva; Kleggetveit, Inge Petter; Kaluza, Luisa; Meents, Jannis; Gerlach, Aaron; Lin, Zhixin; Winterpacht, Andreas; Dragicevic, Elena; et al. (EBioMedicine, 2018)
BACKGROUND: Small fiber neuropathy (SFN) is a severe and disabling chronic pain syndrome with no causal and limited symptomatic treatment options. Mechanistically based individual treatment is not available. We report an in-vitro predicted individualized treatment success in one therapy-refractory Caucasian patient suffering from SFN for over ten years. METHODS: Intrinsic excitability of human induced pluripotent stem cell (iPSC) derived nociceptors from this patient and respective controls were recorded on multi-electrode (MEA) arrays, in the presence and absence of lacosamide. The patient's pain ratings were assessed by a visual analogue scale (10: worst pain, 0: no pain) and treatment effect was objectified by microneurography recordings of the patient's single nerve C-fibers. FINDINGS: We identified patient-specific changes in iPSC-derived nociceptor excitability in MEA recordings, which were reverted by the FDA-approved compound lacosamide in vitro. Using this drug for individualized treatment of this patient, the patient's pain ratings decreased from 7.5 to 1.5. Consistent with the pain relief reported by the patient, microneurography recordings of the patient's single nerve fibers mirrored a reduced spontaneous nociceptor (C-fiber) activity in the patient during lacosamide treatment. Microneurography recordings yielded an objective measurement of altered peripheral nociceptor activity following treatment. INTERPRETATION: Thus, we are here presenting one example of successful patient specific precision medicine using iPSC technology and individualized therapeutic treatment based on patient-derived sensory neurons.
EVALuna2:35119

Pattern of Functional TTX-Resistant Sodium Channels Reveals a Developmental Stage of Human iPSC- and ESC-Derived Nociceptors - Eberhardt, Esther; Havlicek, Steven; Schmidt, Diana; Link, Andrea; Neacsu, Cristian; Kohl, Zacharias; Hampl, Martin; Kist, Andreas; Klinger, Alexandra; Nau, Carla; Schüttler, Jürgen; Alzheimer, Christian; et al. (Stem Cell Reports, 2015)
Human pluripotent stem cells (hPSCs) offer the opportunity to generate neuronal cells, including nociceptors. Using a chemical-based approach, we generated nociceptive sensory neurons from HUES6 embryonic stem cells and retrovirally reprogrammed induced hPSCs derived from fibroblasts. The nociceptive neurons expressed respective markers and showed tetrodotoxin-sensitive (TTXs) and -resistant (TTXr) voltage-gated sodium currents in patch-clamp experiments. In contrast to their counterparts from rodent dorsal root ganglia, TTXr currents of hPSC-derived nociceptors unexpectedly displayed a significantly more hyperpolarized voltage dependence of activation and fast inactivation. This apparent discrepancy is most likely due to a substantial expression of the developmentally important sodium channel NAV1.5. In view of the obstacles to recapitulate neuropathic pain in animal models, our data advance hPSC-derived nociceptors as a better model to study developmental and pathogenetic processes in human nociceptive neurons and to develop more specific small molecules to attenuate pain.
EVALuna2:2465

Propacetamol-Induced Injection Pain Is Associated with Activation of Transient Receptor Potential Vanilloid 1 Channels - Schillers, Florian; Eberhardt, Esther; Leffler, Andreas; Eberhardt, Mirjam (Journal of Pharmacology and Experimental Therapeutics, 2016)
Propacetamol (PPCM) is a prodrug of paracetamol (PCM), which was generated to increase water solubility of PCM for intravenous delivery. PPCM is rapidly hydrolyzed by plasma esterases to PCM and diethylglycine and shares some structural and metabolic properties with lidocaine. Although PPCM is considered to be comparable to PCM regarding its analgesic properties, injection pain is a common side effect described for PPCM but not PCM. Injection pain is a frequent and unpleasant side effect of numerous drugs in clinical use, and previous reports have indicated that the ligand gated ion channels transient receptor potential ankyrin 1 (TRPA1) and transient receptor potential vanilloid 1 (TRPV1) can mediate this effect on sensory neurons. This study aimed to investigate molecular mechanisms by which PPCM, in contrast to PCM, causes injection pain. Therefore, human TRPV1 and TRPA1 receptors were expressed in human embryonic kidney 293 cells and investigated by means of whole-cell patch clamp and ratiometric calcium imaging. PPCM (but not PCM) activated TRPV1, sensitized heat-induced currents, and caused an increase in intracellular calcium. In TRPA1-expressing cells however, both PPCM and PCM evoked calcium responses but failed to induce inward currents. Intracutaneous injection of PPCM, but not of PCM, in human volunteers induced an intense and short-lasting pain and an increase in superficial blood flow, indicating activation of nociceptive C fibers and subsequent neuropeptide release. In conclusion, activation of human TRPV1 by PPCM seems to be a relevant mechanism for induction of pain upon intracutaneous injection and thus also for pain reported as an adverse side effect upon intravenous administration.
EVALuna2:16738

Reactive metabolites of acetaminophen activate and sensitize the capsaicin receptor TRPV1 - Eberhardt, Mirjam J.; Schillers, Florian; Eberhardt, Esther; Risser, Linus; De La Roche, Jeanne; Herzog, Christine; Echtermeyer, Frank; Leffler, Andreas (Scientific Reports, 2017)
The irritant receptor TRPA1 was suggested to mediate analgesic, antipyretic but also pro-inflammatory effects of the non-opioid analgesic acetaminophen, presumably due to channel activation by the reactive metabolites parabenzoquinone (pBQ) and N-acetyl-parabenzoquinonimine (NAPQI). Here we explored the effects of these metabolites on the capsaicin receptor TRPV1, another redox-sensitive ion channel expressed in sensory neurons. Both pBQ and NAPQI, but not acetaminophen irreversibly activated and sensitized recombinant human and rodent TRPV1 channels expressed in HEK 293 cells. The reducing agents dithiothreitol and N-acetylcysteine abolished these effects when co-applied with the metabolites, and both pBQ and NAPQI failed to gate TRPV1 following substitution of the intracellular cysteines 158, 391 and 767. NAPQI evoked a TRPV1-dependent increase in intracellular calcium and a potentiation of heat-evoked currents in mouse spinal sensory neurons. Although TRPV1 is expressed in mouse hepatocytes, inhibition of TRPV1 did not alleviate acetaminophen-induced hepatotoxicity. Finally, intracutaneously applied NAPQI evoked burning pain and neurogenic inflammation in human volunteers. Our data demonstrate that pBQ and NAQPI activate and sensitize TRPV1 by interacting with intracellular cysteines. While TRPV1 does not seem to mediate acetaminophen-induced hepatotoxicity, our data identify TRPV1 as a target of acetaminophen with a potential relevance for acetaminophen-induced analgesia, antipyresia and inflammation.
EVALuna2:36279

SCN10A Mutation in a Patient with Erythromelalgia Enhances C-Fiber Activity Dependent Slowing - Kist, Andreas; Sagafos, Dagrun; Rush, Anthony M.; Neacsu, Cristian; Eberhardt, Esther; Schmidt, Roland; Lunden, Lars Kristian; Orstavik, Kristin; Kaluza, Luisa; Meents, Jannis; Zhang, Zhiping; Carr, Thomas Hedley; et al. (PLoS ONE, 2016)
Gain-of-function mutations in the tetrodotoxin (TTX) sensitive voltage-gated sodium channel (Nav) Nav1.7 have been identified as a key mechanism underlying chronic pain in inherited erythromelalgia. Mutations in TTX resistant channels, such as Nav1.8 or Nav1.9, were recently connected with inherited chronic pain syndromes. Here, we investigated the effects of the p.M650K mutation in Nav1.8 in a 53 year old patient with erythromelalgia by microneurography and patch-clamp techniques. Recordings of the patient's peripheral nerve fibers showed increased activity dependent slowing (ADS) in CMi and less spontaneous firing compared to a control group of erythromelalgia patients without Nav mutations. To evaluate the impact of the p.M650K mutation on neuronal firing and channel gating, we performed current and voltage-clamp recordings on transfected sensory neurons (DRGs) and neuroblastoma cells. The p.M650K mutation shifted steady-state fast inactivation of Nav1.8 to more hyperpolarized potentials and did not significantly alter any other tested gating behaviors. The AP half-width was significantly broader and the stimulated action potential firing rate was reduced for M650K transfected DRGs compared to WT. We discuss the potential link between enhanced steady state fast inactivation, broader action potential width and the potential physiological consequences.
EVALuna2:16730

Sodium channel slow inactivation interferes with open channel block - Hampl, Martin; Eberhardt, Esther; o' Reilly, Andrias; Lampert, Angelika (Scientific Reports, 2016)
Mutations in the voltage-gated sodium channel Nav1.7 are linked to inherited pain syndromes such as erythromelalgia (IEM) and paroxysmal extreme pain disorder (PEPD). PEPD mutations impair Nav1.7 fast inactivation and increase persistent currents. PEPD mutations also increase resurgent currents, which involve the voltage-dependent release of an open channel blocker. In contrast, IEM mutations, whenever tested, leave resurgent currents unchanged. Accordingly, the IEM deletion mutation L955 (?L955) fails to produce resurgent currents despite enhanced persistent currents, which have hitherto been considered a prerequisite for resurgent currents. Additionally, ?L955 exhibits a prominent enhancement of slow inactivation (SI). We introduced mutations into Nav1.7 and Nav1.6 that either enhance or impair SI in order to investigate their effects on resurgent currents. Our results show that enhanced SI is accompanied by impaired resurgent currents, which suggests that SI may interfere with open-channel block.
EVALuna2:16732

Store-operated calcium entry is reduced in spastin-linked hereditary spastic paraplegia - Winner, Beate; Rizo Garza, Tania; Gebhardt, Lisa; Riedlberger, Julia; Eberhardt, Esther; Fester, Lars; Alansary, Dalia; Winkler, Jürgen; Turan, Sören; Arnold, Philipp; Niemeyer, Barbara; Fischer, Michael (2022)
Pathogenic variants in SPAST, the gene coding for spastin, are the single most common cause of hereditary spastic paraplegia, a progressive motor neuron disease. Spastin regulates key cellular functions, including microtubule-severing and endoplasmic reticulum-morphogenesis. However, it remains unclear how alterations in these cellular functions due to SPAST pathogenic variants result in motor neuron dysfunction. Since spastin influences both microtubule network and endoplasmic reticulum structure, we hypothesized that spastin is necessary for the regulation of Ca2+ homeostasis via store-operated calcium entry. Here, we show that the lack of spastin enlarges the endoplasmic reticulum and reduces store-operated calcium entry. In addition, elevated levels of different spastin variants induced clustering of STIM1 within the endoplasmic reticulum, altered the transport of STIM1 to the plasma membrane and reduced store-operated calcium entry, which could be rescued by exogenous expression of STIM1. Importantly, store-operated calcium entry was strongly reduced in induced pluripotent stem cell-derived neurons from hereditary spastic paraplegia patients with pathogenic variants in SPAST resulting in spastin haploinsufficiency. These neurons developed axonal swellings in response to lack of spastin. We were able to rescue both store-operated calcium entry and axonal swellings in SPAST patient neurons by restoring spastin levels, using CRISPR/Cas9 to correct the pathogenic variants in SPAST. These findings demonstrate that proper amounts of spastin are a key regulatory component for store-operated calcium entry mediated Ca2+ homeostasis and suggest store-operated calcium entry as a disease relevant mechanism of spastin-linked motor neuron disease.Rizo et al. use iPSC-derived neurons from patients to investigate how pathogenic variants in SPAST give rise to hereditary spastic paraplegia. They show that dysregulation of spastin, a microtubule- and ER-remodelling protein encoded by SPAST, alters the dynamics of the ER, resulting in aberrant Ca2+ regulation.
Keywords: spastin; STIM1; microtubules; endoplasmic reticulum; store-operated calcium entry

Th17 Lymphocytes Induce Neuronal Cell Death in a Human iPSC-Based Model of Parkinson's Disease - Sommer, Annika; Marxreiter, Franz; Krach, Florian; Fadler, Tanja; Grosch, Janina; Maroni, Michele; Gräf, Daniela; Eberhardt, Esther; Riemenschneider, Markus J.; Yeo, Gene W.; Kohl, Zacharias; Xiang, Wei; et al. (Cell Stem Cell, 2019)
EVALuna2:203042

Th17 Lymphocytes Induce Neuronal Cell Death in a Human iPSC-Based Model of Parkinson's Disease - Sommer, Annika; Maxreiter, Franz; Krach, Florian; Fadler, Tanja; Grosch, Janina; Maroni, Michele; Graef, Daniela; Eberhardt, Esther; Riemenschneider, Markus J.; Yeo, Gene W.; Kohl, Zacharias; Xiang, Wei; et al. (Cell Stem Cell, 2018)
Parkinson's disease (PD) is a neurodegenerative disorder characterized by the progressive degeneration of midbrain neurons (MBNs). Recent evidence suggests contribution of the adaptive immune system in PD. Here, we show a role for human T lymphocytes as cell death inducers of induced pluripotent stem cell (iPSC)-derived MBNs in sporadic PD. Higher Th17 frequencies were found in the blood of PD patients and increased numbers of T lymphocytes were detected in postmortem PD brain tissues. We modeled this finding using autologous co-cultures of activated T lymphocytes and iPSC-derived MBNs of sporadic PD patients and controls. After co-culture with T lymphocytes or the addition of IL-17, PD iPSC-derived MBNs underwent increased neuronal death driven by upregulation of IL-17 receptor (IL-17R) and NF kappa B activation. Blockage of IL-17 or IL-17R, or the addition of the FDA-approved anti-IL-17 antibody, secukinumab, rescued the neuronal death. Our findings indicate a critical role for IL-17-producing T lymphocytes in sporadic PD.
EVALuna2:35782

β1 and β3 subunits amplify mechanosensitivity of the cardiac voltage-gated sodium channel Nav1.5 - Maroni, Michele; Körner, Jannis; Schüttler, Jürgen; Winner, Beate; Lampert, Angelika; Eberhardt, Esther (Pflügers Archiv: European Journal of Physiology, 2019)
In cardiomyocytes, electrical activity is coupled to cellular contraction, thus exposing all proteins expressed in the sarcolemma to mechanical stress. The voltage-gated sodium channel Nav1.5 is the main contributor to the rising phase of the action potential in the heart. There is growing evidence that gating and kinetics of Nav1.5 are modulated by mechanical forces and pathogenic variants that affect mechanosensitivity have been linked to arrhythmias. Recently, the sodium channel β1 subunit has been described to stabilise gating against mechanical stress of Nav1.7 expressed in neurons. Here, we tested the effect of β1 and β3 subunits on mechanosensitivity of the cardiac Nav1.5. β1 amplifies stress-induced shifts of V1/2 of steady-state fast inactivation to hyperpolarised potentials (ΔV1/2: 6.2 mV without and 10.7 mV with β1 co-expression). β3, on the other hand, almost doubles stress-induced speeding of time to sodium current transient peak (Δtime to peak at − 30 mV: 0.19 ms without and 0.37 ms with β3 co-expression). Our findings may indicate that in cardiomyocytes, the interdependence of electrical activity and contraction is used as a means of fine tuning cardiac sodium channel function, allowing quicker but more strongly inactivating sodium currents under conditions of increased mechanical stress. This regulation may help to shorten action potential duration during tachycardia, to prevent re-entry phenomena and thus arrhythmias.
CRIS-Team Scopus Importer:2019-11-26
Keywords: Cardiac ion channel; Mechanosensitivity; Patch-clamp; Sodium channel